Swell observations on Soviet research vessels during Monsoon Experiment MONEX 1977-Part II : Arabian Sea - MUKHERJEE, A. K.; SIVARAMAKRISIINAN, T. R. (MAUSAM, 1980)
The results of the analysis of swell observations by Russian ships in Arabian Sea are presented here: The broad conclusions are : (1) The height of swell steadily increases when we move from equator to Lat. 12 deg. N during both June and July. (2) There is no significant variation in the height of swells in scale between Lat. 10 deg. N and 15 deg. N once the monsoon sets in. (3) No diurnal variation was observed in the height of swells.